Evaluasi Pelaksanaan Tari Kreasi dalam Mengembangkan Kecerdasan Kinestetik Anak di TK Negeri Pembina Lubuk Pakam - Yola Aritonang, Cindy; Amelianda, Amelianda; Gabriela, Mulyani; Dhara, Nabila; Sijabat, Nurbetti; Yus, Anita; Khodijah Lubis, Siti (Journal of Comprehensive Science, 2024)
This research aims to evaluate the implementation of creative dance as a medium for developing kinesthetic intelligence in early childhood at the Pembina Lubuk Pakam State Kindergarten. Creative dance was chosen because it is relevant in improving children's gross motor skills, coordination and creativity. The evaluation method uses the CIPP model which includes context, input, process and product, with data collection techniques through observation, interviews and documentation. The evaluation results show that the implementation of creative dance has helped children improve gross and fine motor skills, as well as build self-confidence and creativity. However, obstacles were found such as limited facilities and lack of program support from parents. The implication of this research is the importance of optimizing supporting facilities and increasing teacher competency to ensure the success of the program. Thus, creative dance has proven to be an effective means of supporting the kinesthetic development of young children and enriching their learning experiences in an educational environment.